2019
DOI: 10.1016/j.npe.2019.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Noise in nanopore sensors: Sources, models, reduction, and benchmarking

Abstract: Label-free nanopore sensors have emerged as a new generation technology of DNA sequencing and have been widely used for single molecule analysis. Since the first α-hemolysin biological nanopore, various types of nanopores made of different materials have been under extensive development. Noise represents a common challenge among all types of nanopore sensors. The nanopore noise can be decomposed into four components in the frequency domain (1/f noise, white noise, dielectric noise, and amplifier noise). In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 90 publications
0
48
1
3
Order By: Relevance
“…S2A in the ESI † provides the schematic of main sources in PSD noises including four components, i.e., icker (also referred to as 1/f), thermal, dielectric and capacitance noises. 22,23 First, a potential bias was applied across the nanopore chip, which led to an increased 1/f noise and a steeper slope of the 1/f dependent noise along with increasing the potential (Fig. 3C).…”
Section: Resultsmentioning
confidence: 99%
“…S2A in the ESI † provides the schematic of main sources in PSD noises including four components, i.e., icker (also referred to as 1/f), thermal, dielectric and capacitance noises. 22,23 First, a potential bias was applied across the nanopore chip, which led to an increased 1/f noise and a steeper slope of the 1/f dependent noise along with increasing the potential (Fig. 3C).…”
Section: Resultsmentioning
confidence: 99%
“…The sensitivity of nanopore sensors greatly depends on electrical current noise that coexists with translocation signal. [ 90–93 ] Researches have been focused on two sources of noise in nanopore sensors: 1) dielectric noise and 2) flicker noise (or 1/ f noise). The dielectric noise dominates at high frequency (>1 kHz) in power spectrum density and significantly affects I RMS .…”
Section: Sensitivitymentioning
confidence: 99%
“…As can be seen from the aforementioned literature review, the current studies mainly focus on oil droplets in water phase, while the study of water droplets in oil phase is not reported. However, in many engineering fields, especially oil production, oil‐water separation, and oil pollution treatment fields, the motion behavior of water droplets in oil field is more desirable [48–50] . The objective of this work is to fill this gap by finding a smart water droplet micro robot which can go deep into cracks and propel the residual oil out of reservoir.…”
Section: Figurementioning
confidence: 99%